Surgical treatment of the perihilar cholangiocarcinoma with portal vein invasion - Popov, O. (Journal of Education, Health and Sport, 2023)
Background. Perichilar cholangiocarcinoma is a rare type of malignant neoplasm and is 3-7 cases per 100,000 population. Surgical method is the only radical method of treatment, allowing to improve long-term survival results. One of the important and characteristic features of perihilar cholangiocarcinoma is tumor invasion to the area of the portal vein bifurcation, which occurs in 30–45% of cases. Portal vein invasion is the one of the main causes of perihilar cholangiocarcinoma irresectability. However, innovative surgical technologies allow resection of the liver with resection and reconstruction of the portal vein with acceptable mortality. The aim. The aim of our study was to asses results of surgical treatment of perihilar cholangiocarcinoma with (Group 1) and without (Group 2) portal vein invasion. Materials and methods. From 2003 to January 2023 in the Department of Surgery and Liver Transplantation of the Ukrainian National Institute of Surgery and Transplantation, 208 patients with perihilar cholangiocarcinoma underwent major extended liver resections. We compared 93 (46%) patients who received extended liver resection with portal vein resection (Group 1) with 115 (54%) patients who underwent liver resections without vascular reconstructions (Group 2). The average Ca 19–9 in the group 1 was 288 (8 – 1000) U/ml, in the group 2 –262 (10 – 612) U/ml. The level of total bilirubin in patients of the group 1 was 312 (43 – 621) mcmol/l, in the group 2 – 267 (10 – 612) mcmol/l. In view of this, in the preoperative period, 190 (91,3%) patients underwent decompression of the bile ducts, using percutaneous transhepatic cholangiostomy (PTBD) or retrograde endobiliary stenting. For patients with small remnant liver volume less than 40 %, in 80(38,5%) cases we did preoperative PVE of a resected part of the liver. In 9 cases we made simultaneous PVE and PTBD. When choosing the volume of surgical intervention, we proceeded from the tumor type of Bismuth-Corlette classification, invasion into the portal vessels and the depth of the liver lesion. The portal vein reconstruction was in all cases performed in an “end-to-end”. In all cases we made extended lymphadenectomy. Results. All complications were classified according to the Dindo-Clavien classification. Postoperative mortality in the main group was 11.5%. The overall 1, 3, 5-year survival in the group 1 was 96%, 68,3%, 57,4%, respectively. 1, 3, 5-year survival rate in the comparison group 2 was 98,4%, 76,7%, 47,3%, respectively. Conclusions. Aggressive tactics of surgical treatment of perihilar cholangiocarcinoma provides maximum radicality, allows to increase resectability in case of tumor invasion of the portal vein with acceptable mortality and long-term survival.